(untitled) (Archives of Clinical and Medical Case Reports, 2021)
Persistent trigeminal artery (PTA), commonest among fetal carotid-vertebrobasilar anastomosis encountered in adult life, is an incidental finding but has often been associated with trigemino-cavernous fistula besides cranial nerve palsies, trigeminal neuralgia, hemifacial spasms, intracranial vascular pathologies like aneurysms, arteriovenous malformations posterior circulation, as TIAs or stroke. We present here an acute posterior circulation stroke and a chronic anterior circulation stroke associated with (PTA), in this case report.